The CAG polymorphism in androgen receptor (AR) gene impacts the moral permissibility of harmful behavior in females. (June 2017) - Gong, Pingyuan; Fang, Pengpeng; Yang, Xing; Ru, Wenzhao; Wang, Bei; Gao, Xiaocai; Liu, Jinting
Highlights: Androgen receptor (AR) gene impacts moral permissibility of harmful behavior. Females with the S allele judge harmful utilitarian acts as permissible. Females with the S allele judge unintentionally harmful acts as permissible. Abstract: The moral permissibility of harm is strikingly varied among individuals. In light of the connection between testosterone levels and utilitarian moral judgment, this study examined to what extent a CAG polymorphism in the androgen receptor gene, a genetic polymorphism with the ability to regulate testosterone function, contributes to individual differences in moral judgment. Four hundred and thirty-nine Chinese Han participants completed permissibility ratings of harm in moral dilemmas and moral transgression scenarios. Results showed a significant association between the CAG polymorphism and moral permissibility of harm in females. Females with more copies of the S allele, which is associated with higher availability of testosterone, were more likely to judge harmful utilitarian acts and unintentionally harmful acts as permissible, while these effects were absent in males. The findings provide the first evidence for a link between the androgen receptor gene and moral judgment and highlight the role of androgens in moral foundations.